DESAIN INTERACTIVE PSYCHOEDUCATIONAL CENTER DENGAN PENDEKATAN MENTAL WELLNESS TOURISM DI KABUPATEN MALANG - Sabrina, Risa (Jurnal Mahasiswa Departemen Arsitektur, 2025)
Mental health issues in Indonesia, especially in adolescents and young adults, are showing a significant increase. National surveys indicate that many individuals experience mental disorders but do not access adequate mental health services. Therefore, mental health education and promotion facilities are needed. This final project designs an Interactive Psychoeducational Center with the thematic approach of Mental Wellness Tourism, which combines disease prevention tourism with the four pillars of mental well-being-Creativity, Growth, Rejuvenation, and Connection. Methodologically, the design follows the intuitionism paradigm: the intuitive induction process on the site gives rise to the theme “From Awareness to Mindfulness”, which is then translated into the principles of organic forms, gradual space transitions, and strong interior-exterior connections. Thus, this design not only answers spatial needs based on the space program, but also becomes a social intervention media that promotes the importance of literacy and awareness of mental health in a holistic and fun way.